Differential effects of ceramide species on exocytosis in rat PC12 cells - Tang, Ning; Ong, Wei-Yi; Zhang, En-Ming; Chen, Peng; Yeo, Jin-Fei (Experimental brain research, 2007)
Increases in several ceramide species have been shown by non-targeted lipid profiling (lipidomics) of the rat hippocampus after kainate lesions (Guan et al. FASEB J 20:1152-1161, 2006). This study was carried out to examine possible effects of ceramide species on exocytosis. Significant increase in membrane capacitance in voltage-clamped rat pheochromocytoma (PC12) cells, an indication of exocytosis, was detected immediately after external application of C2, C6, and C18 ceramide. In contrast, no increase in capacitance was found after addition of C16 and C20 ceramide, or DMSO vehicle. The effect of ceramide on exocytosis was dependent on the integrity of lipid rafts. Treatment of cells with the cholesterol binding agent/disruptor of lipid rafts, methyl beta cyclodextrin, prior to addition of C18 ceramide suppressed the increase in capacitance induced by this lipid species. The ability of C2, C6 and C18 ceramide to trigger exocytosis was confirmed using total internal reflection fluorescence microscopy (TIRFM) experiments. External application of these species caused an exponential decrease in the number of subplasmalemmal neuropeptide Y (NPY)-enhanced green fluorescence protein (EGFP) labeled vesicles, indicating exocytosis. Interestingly, C18 is also the ceramide species that showed the greatest increase in the rat hippocampus after kainate excitotoxicity. It is postulated that C18 ceramide might facilitate exocytosis of glutamate from damaged neurons, thus propagating neuronal injury.